Spare Part Warehouse Management Analysis Using 5S Approach and FIFO System - Mila Faila Sufa; Makruf Kausar Mulyana (LPPM Universitas Duta Bangsa Surakarta, 2021)
PT. Z is a company located outside Java, to be precise in the industrial area of Batam city, whose business process is to make to order. This company has a mission to build up goodwill and trust from their customer upon uncompromising quality and on time delivery that come with very competitive pricing. To achieve this mission, PT. Z has an adequate material and spare part supply system so that when there is an order from a customer, it will be done immediately without waiting for the spare part to arrive. The problem faced by this company is that there are many spare parts that are arranged untidy and difficult to find, besides that some items have been damaged due to too long accumulation in the warehouse. The application of the 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) approach and FIFO system in spare part management warehouse is used to reduce time waste caused by inefficient layout of spare parts. After applying these two methods in managing spare parts, there are some decreases in the activity time to find fast moving spare parts from 1.782 minutes to 0.983 minutes and the activity to search fast moving spare parts from 1.688 minutes to 0.9 minutes. While for the slow moving parts there is a time decrease of 0.881 minutes for storage activity and 1.471 minutes to search activity. For fast moving spare parts and slow moving spare parts both have increased efficiency. The percentage of store activity efficiency are 81% and 62%, while the efficiency of the activity to store spare parts are 87% and 55%. Fast moving parts and slow moving parts both have an efficient and effective layout with a systematic storage method.